TURN TAKING IN THE CONVERSATION PRODUCED BY MEMBERS OF ENGLISH SPEAKING COMMUNITY AT SURABAYA STATE UNIVERSITY - DEWI, FITRIYAH (LANGUAGE HORIZON, 2016)
Abstract English Speaking Community is the community which exists in Surabaya State University which is functioned to improve the student’s speaking skill. In Discourse Analysis, the conversation produced by the members of English Speaking Community has created phenomena of turn taking. This study focuses on the turn taking phenomena which emerge in the member’s conversation. The purposes of the study are: to describe the categories of turn taking  that happen in the conversation produced by the member of English speaking community; to find out how the phenomena of turn taking strategies through interruption, overlap, and backchannel happen during the conversation. This study uses qualitative approach. Observing directly and video recording are chosen to collect the data. The findings of the study show that adjacency pairs and repair are the most categories that emerge in the conversation among participants. Overlap and interruption happen in the same time but in different purpose, if overlap use to show the enthusiasm and closeness while interruption can be indicate as the power in the conversation. The participants use the signal of understands, listens the participant’s opinion, and the way they cannot answer the question from the leader.